Post-Sample Prediction Tests for the Efficient Method of Moments - Pieter J. van der Sluis (Tinbergen Institute, 1997)
In this paper a post-sample prediction test is derived forestimators based on the Efficient Method of Moments. The mainadvantage of this particular test over other stability tests isthat no time-consuming estimation of the structural parameters forthe post-sample is needed. The asymptotic properties of the testand local power properties against certain alternatives are deduced.Using the Efficient Method of Moments methodology, anapplication is made to stochastic volatility models for theBritish pound versus Canadian dollar exchange rates. The breakpointfor the stability test is a priori set at September 16th 1992,when Britain was forced to leave the European Monetary UnionExchange Rate System.
Keywords: 330; Schätztheorie; Wechselkurs; Volatilität; Großbritannien; Kanada